Diseases of the oral mucosa: study guide and review - Schmidt, E. Enno (Springer, 2022)
This textbook details the latest diagnostic and management options available when treating patients with diseases affecting the oral mucosa. It comprehensively covers the content required to successfully pass dermatology and stomatology board examinations, while being a valuable resource for dentistry trainees. Chapters cover aspects of mucosal immunity and clinical scores along with a range of diseases. Didactic features including learning objectives enable the reader to better extrapolate the key concepts covered in each chapter. Diseases of the Oral Mucosa: Study Guide and Review presents an in depth overview of the latest diagnostic tools and management options available for diseases of the oral mucosa and is an ideal resource for trainee and practising dentists, dermatologists and stomatologists preparing to sit board examinations.